Study on mechanical, electronic and optical properties of Pb-free double halide perovskites In2TiX6 (X = Cl, Br, I) for solar cells based on first-principles. (March 2021) - Zhao, Xian-Hao; Tang, Yan-Lin; Tang, Tian-Yu; Diao, Xin-Feng; Gao, Li-Ke; Xie, Quan; Shi, Bin; Yuan, Li; Lu, Li-Min
Graphical abstract: Highlights: First-principles method was adopted to study the mechanical, electronic and optical properties of double perovskites In2 TiX6 (X = Cl, Br, I). In2 TiX6 (X = Cl, Br, I) are thermodynamically and mechanically stable. In2 TiX6 (X = Cl, Br, I) are ductile materials. The compound In2 TiI6 can be a potential candidate for excellent light absorbing material. Abstract: In recent years, perovskite solar cells have attracted the attention of many researchers due to their advantages such as high conversion efficiency, simple manufacturing process and low cost, and have become an important research direction in the field of new energy batteries. At the same time, it is also a very promising new type of solar cells. In this paper, the geometric characteristics, mechanical properties, electronic properties and optical properties of three perovskites In2 TiCl6, In2 TiBr6 and In2 TiI6 were studied by using first-principles. The Poisson and Pugh's ratios show the ductile characteristics of In2 TiX6 (X = Cl, Br, I). The mechanical stability of studied compounds has been confirmed by the Born stability criteria. Moreover, the thermodynamic stability has been proved by the negative formation enthalpy and cohesive energy. In2 TiCl6 and In2 TiBr6 are indirect band gap semiconductors with band gap values 2.15 and 2.12 eV, respectively, and In2 TiI6 is a direct band gap semiconductor with band gap value 1.24 eV. Theoretical calculations showed that In2 TiI6 has better absorption capacity than In2 TiCl6 and In2 TiBr6 in the near ultraviolet and visible light regions. The results demonstrate that the compound In2 TiI6 can be a potential candidate for excellent light absorbing material.